Differences in health literacy related to gestational weight gain and children’s birth weight according to maternal nativity status in the Japan Environment and Children’s Study (JECS): a longitudinal cohort study - Zentaro Yamagata; Takeo Nakayama; Reiko Kishi; Nobuo Yaegashi; Shuichi Ito; Mika Kigawa; Akiko Tsuchida; Mika Ito; Tomomi Tanaka; Kei Hamazaki; Yuichi Adachi; Hidekuni Inadera; et al. (BMJ Open, 2024)
Objectives We examined literacy related to healthy gestational weight gain (GWG) in immigrant and native Japanese mothers and determined whether it is associated with children’s birth weight.Design Longitudinal cohort study.Setting As the baseline survey in the Japan Environment and Children’s Study (JECS), mothers completed self-administered questionnaires distributed by hand during pregnancy. The self-administered questionnaires used in this study were distributed by mail 6 months after delivery. Children’s birth weight, actual GWG and any complications during delivery were recorded by obstetricians collaborating with JECS.Participants Of 97 452 mothers who consented to participate in the JECS during pregnancy between January 2011 and March 2014, 67 953 were included in this study after exclusions for multiple births, multiple instances of consent by the same pregnant woman, miscarriages/stillbirths or withdrawal from the study within 3 years after participating. In total, 324 immigrant mothers and 963 native Japanese mothers were selected by propensity score matching for analysis.Primary and secondary outcome measures Data were collected on maternal literacy related to healthy GWG at the baseline survey, and data on actual GWG and children’s birth weight were collected by obstetricians. The associations of knowledge about healthy GWG and mothers’ actual GWG with maternal nativity status were examined using a χ2 or Student’s t-test.Results More native Japanese mothers than immigrant mothers knew the appropriate GWG and reason the for needing to know this. Actual GWG was significantly higher among the immigrant mothers, but was within the recommended range. The low birthweight (LBW) incidence was significantly higher among the native mothers.Conclusions Immigrant mothers to Japan had less knowledge about appropriate GWG, but their actual GWG was appropriate and they delivered fewer LBW infants than native Japanese mothers. These findings may indicate the presence of other protective factors for pregnancy or delivery among immigrant mothers.